Field Deployment of Low Power High Performance Nodes - Martinez, K; Basford, P; Ellul, J; Clarke, R (2010 IEEE 30th International Conference on Distributed Computing Systems Workshops, 2010)
When deploying a sensor network into a harsh environment the need for high levels of fault tolerance and maximising the usage of available resources become extremely important. This has been achieved by implementing a highly fault tolerant system based on our Gumsense boards. These combine an ARM-based Linux system with an MSP430 for sensing and power-control. It also allows for dynamic schedule modifications based on the available power and can be synchronised with other systems without relying on direct communication, autonomous behaviour in case of total communications failure is also supported. A deployment on Vatnajökull, the largest ice-cap in Europe, has provided a long-term test for the systems and revealed strengths and weaknesses in the design decisions.